2021
DOI: 10.1002/pro.4020
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the beta hairpin motif in the Protein Data Bank

Abstract: The beta hairpin motif is a ubiquitous protein structural motif that can be found in molecules across the tree of life. This motif, which is also popular in synthetically designed proteins and peptides, is known for its stability and adaptability to broad functions. Here, we systematically probe all 49,000 unique beta hairpin substructures contained within the Protein Data Bank (PDB) to uncover key characteristics correlated with stable beta hairpin structure, including amino acid biases and enriched interstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…They are distributed in an impressive number of different folds, such as the β-hairpin repeat proteins [ 65 ]. A very large number of β-turns is found in β-hairpins [ 66 ], but some are without [ 67 ], and a number of β-turns are not found in β-hairpins. It is critical to note that this connecting loop resembles a hairpin and it is logical that β-turns are found inside (as for γ- and α-turns too [ 66 ]), but it is not systematic.…”
Section: The Alpha and The Omega Of The βmentioning
confidence: 99%
“…They are distributed in an impressive number of different folds, such as the β-hairpin repeat proteins [ 65 ]. A very large number of β-turns is found in β-hairpins [ 66 ], but some are without [ 67 ], and a number of β-turns are not found in β-hairpins. It is critical to note that this connecting loop resembles a hairpin and it is logical that β-turns are found inside (as for γ- and α-turns too [ 66 ]), but it is not systematic.…”
Section: The Alpha and The Omega Of The βmentioning
confidence: 99%
“…In our studies, we have also shown the high stability of SSS for 4 types of helical pairs accessed by the MD [15][16][17]. The β-hairpin motif is also characterized by high autonomous stability, which makes this motif popular for producing artificial protein structures with desired properties (hydrogels, antimicrobial peptides) [52][53][54][55].…”
Section: Protein Conformational Stabilitymentioning
confidence: 55%
“…Our design scheme leveraged our recently completed systematic analysis of more than 49,000 β-hairpin motifs in the Protein Data Bank. This analysis identified position-specific amino acid preferences in the strand and turn regions ( 14 ). Using this information, we designed two ribosomally encoded 20–amino acid cyclic β-hairpin peptide libraries ( Fig.…”
Section: Resultsmentioning
confidence: 99%